COUNTERING UNACCEPTABLE TAX AVOIDANCE THROUGH GENERAL ANTI-AVOIDANCE RULE IN EU TAX LAW - Radić, Irena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
To reduce tax avoidance, most nations use either judicial anti-avoidance doctrines (eg. substance over form doctrine) or legislative anti-avoidance rules that occur in the form of general and specific anti-abuse rules. The specific anti-avoidance rules (SAARs) in most cases simply mechanically deny certain tax benefits under certain conditions and their goal is to prevent avoidance or abuse of specific rules in the tax code. Therefore these rules are not effective in tackling tax avoidance arrangements that exploit tax law loopholes in a way that was unforeseen when the tax law was enacted. A solution for this problem has been found in the general anti-avoidance rule (GAAR) that has been recognized as a “final weapon against all the creative and aggressive tax avoidance scenarios”. In January 2016 the European Commission introduced a proposal for a Council Directive on “rules against tax avoidance practices that directly affect the functioning of the internal market” (Anti Tax Avoidance Directive, ATAD) which was approved in July 2018. One of the measures provided by the ATAD is a general anti-avoidance rule that aims “to tackle abusive tax practices that have not yet been dealt with through specifically targeted provisions”. Apart from EU, many other countries like the United Kingdom, Canada, Australia, New Zealand, China, India, etc. have also introduced GAAR.Considering the great importance of GAAR in tackling tax avoidance, as well as the fact that it does not exist in the tax law of the Republic of Serbia, this article will analyze GAAR in EU tax law. In the first section, we define tax avoidance and tax evasion, distinguishing the two terms, and answer the question “why do we need GAAR”. In the second part, we present the elements of the GAAR and the consequences of its application. Finally, in the third part, this article addresses the issue of legal certainty with regard to the application of GAAR. The subject of the analysis will be the ATAD’s GAAR, and the case-law of the European Court of Justice in tax avoidance cases in the context of abuse of Union law.
Keywords: tax avoidance; tax evasion; general anti-avoidance rule; specific anti-avoidance rules; non-genuine arrangements; tax reduction purpose; abuse of law